Dynamic Behavior of Steel Bolted Flush End Plate Beam-to-Column Joints During Progressive Collapse - Haidar, Badia; Loho, Ghandi; ALhaj, Khudr (Latakia University Journal -Engineering Sciences Series, 2020)
Bolted beam-to-column joints are an essential element in the performance of steel structures under exceptional loading conditions such as explosions and vehicle collisions due to the risk of a progressive collapse. The research presented in this paper processes the dynamic behavior of steel bolted flush end plate beam-to-column joints during progressive collapse. to achieve this goal, a dynamic analytical study was performed using a mechanical model created using the ABAQUS finite element program. Parametric study was performed using numerical model to investigate the effect of column load release time on the dynamic response of the studied model. the dynamic response of the joint was studied under the influence of the sudden loss of the column. This response was defined as the relationship between the initial vertical load in the column and the maximum dynamic vertical transition resulting from the release of this load. Based on the dynamic and static response obtained, the values ​​of dynamic increase factors were calculated based on the strength of the studied joint and compared with the values ​​calculated according to the data of the American code (DOD). in the end, a simplified relationship was established that allows the determination of Dynamic Increased Factors (DIFs) of the studied connection in the stage cable action. تشكل الوصلات جائز-عمود المنفذة بالبراغي عنصراً جوهرياً في أداء المنشآت الفولاذية تحت شروط التحميل الاستثنائية كالانفجارات واصطدام العربات بسبب خطر حدوث ما يعرف بالانهيار التدرجي.(progressive collapse) يعالج البحث المقدّم في هذه الورقة السلوك الديناميكي للوصلات الفولاذية جائز-عمود المنفذة بالبراغي وصفائح جبهية غير بارزة أثناء الانهيار التدرجي. لتحقيق هذا الهدف، تم إنجاز دراسة تحليلية ديناميكية باستخدام نموذج ميكانيكي (mechanical model) تم إنشاؤه باستخدام برنامج العناصر المنتهية ABAQUS. تم إنجاز دراسة بارامترية باستخدام النموذج العددي للتحري عن تأثير زمن تفريغ حمولة العمود على الاستجابة الديناميكية للنموذج المدروس. تمت دراسة الاستجابة الديناميكية للوصلة تحت تأثير الفقدان الفجائي للعمود وقد تم تعريف هذه الاستجابة كعلاقة بين الحمولة الشاقولية الابتدائية في العمود والانتقال الشاقولي الديناميكي الأعظمي الناتج عن تفريغ هذه الحمولة. استنادا إلى الاستجابة الديناميكية و الستاتيكية التي تم الحصول عليها تم حساب قيم معامل التضخيم الديناميكي القائم على القوة للوصلة المدروسة وتمت مقارنتها مع القيم المحسوبة وفقا لمعطيات الكود الأمريكي (DOD) . في النهاية، تم وضع علاقة مبسطة تسمح بتحديد معامل التضخيم الديناميكي القائم على القوة للوصلة المدروسة في مرحلة العمل الكابلي.